Development of lipL32 real-time PCR combined with an internal and extraction control for pathogenic Leptospira detection. - Ahmed A Ahmed (PLoS ONE, 2020)
At least two real-time PCRs for the early diagnosis of leptospirosis have been described, evaluated and validated. However, at least one other report suggested adaptation and modification of primers and probes used in these assays since additional Leptospira species have been described and the primers and probe in use possess a serious mismatch to corresponding target sequence. In this study we developed a real-time PCR for detection of pathogenic Leptospira based on the lipL32 gene. The present method consists of generic primers and probes based on target sequence of 10 pathogenic Leptospira species including Leptospira interrogans. The hybridization, annealing and extension temperature (60°C) were optimized as the optimal temperature of the DNA polymerase enzyme which is used in the amplification reaction. The present assay has a high analytical sensitivity and specificity; the calculated diagnostic sensitivity and specificity were 93.0% and 98.3% respectively. Moreover, the present method includes an internal control which enables easy detection of false negative results and an optional extraction control which enables the estimation of the DNA extraction efficiency.